A visual study on illustration traditional herbs guidebook / Nurzayana Zaharudin - Zaharudin, Nurzayana (2019)
Malay traditional herbs, is derived whether from a plant nor flower that have been practiced and applied by the Malays in their culture in order to maintaining the healthy life and to prevent for an illness. All herbs that exist in Malaysia has it’s own benefits and values existing to help humans live a healthy life. Herbs have been proved as a useful plant that can be applied in daily life such as through cooking, beauty, medicine & etc. Some traditional herbs is still practic or applied until now even less. Speaking of herbs it is not only applicable towards old people rather it is addressed to even younger generation nowdays regardless of ages. The aim of this study is to study the use of illustrations in traditional Malay herbs guidebook purposely to maintaining and introduce towards the modern generation which is now increasingly forgotten about the values of traditional Malay herbs heritage. The objective in this study is to analyse or studying types of layout design which is being included in Malay herbs guide book that are available on the market and to produce an illustration guide book of traditional herbs to attract and maintaining the cultural purposes. Therefore, the qualitative method has been used and applied throughout this research.